Pemetaan Kawasan Terdampak Akibat Lahar Dingin Gunung Marapi dan Sekitarnya Menggunakan Citra Satelit Sentinel -2: (Studi Kasus: Kecamatan Sungai Pua, Kabupaten Agam) - Reni Puspita Sari; Dwi Arini; Dwi Marsiska Driptufany; Fajrin Fajrin; Ilham Armi (Jurnal Sains dan Ilmu Terapan, 2025)
Mount Marapi is one of the active volcanoes in West Sumatra, which erupted on December 3, 2023, followed by heavy rainfall that triggered a cold lava flood. This event caused damage to land, infrastructure, and vegetation around Sungai Pua Subdistrict, Agam Regency. This study aims to analyze vegetation density changes before and after the lahar event and to map the affected areas using Sentinel-2 satellite imagery, applying the Normalized Difference Vegetation Index (NDVI) and spatial overlay methods. The results show a decrease in very dense vegetation from 623.127 ha (42.38%) to 199.095 ha (13.54%), and an increase in poor vegetation from 354.269 ha (24.09%) to 551.566 ha (37.50%). The total vegetation density change reached 734.03 ha out of 1,470.32 ha. Identification of affected areas also indicates that the lahar spread along river channels from the summit to the slopes, with an affected area of 110.832 ha. These areas include agricultural land, plantations, and settlements along the riverbanks that were damaged by volcanic materials.